Assembly and Comparative Analysis of the Complete Mitochondrial Genome of Hippophae salicifolia - Zhefei Zeng; Chunmin Mao; Zhuo Shang; Ngawang Norbu; Ngawang Bonjor; Xiaoyan Jia; Wei Li; Wenju Zhang; Junwei Wang; La Qiong (Biology)
This study reports the first complete mitochondrial genome assembly of Hippophae salicifolia, an ecologically and economically important plant endemic to the Himalayas. The 475,105 bp genome has a 44.80% GC content and an overall AT bias, comprising 74 genes (37 protein-coding, 31 tRNA, three rRNA, and three pseudogenes). We identified extensive repetitive elements, including 188 SSRs, 20 tandem repeats, and 455 dispersed repeats, and explored their potential roles in genome evolution. Codon usage analysis showed a bias for codons ending in A or U, while RNA editing analysis revealed 415 sites that mostly convert hydrophilic to hydrophobic amino acids. Phylogenetic and collinearity analyses clarified evolutionary relationships within Hippophae and uncovered genome rearrangements. In addition, extensive gene transfer was detected between the mitochondrial and chloroplast genomes. Ka/Ks and nucleotide diversity analyses indicate that most genes are under purifying selection, with some possibly undergoing positive selection. Overall, these findings enhance our understanding of the structural and evolutionary features of the H. salicifolia mitochondrial genome and provide valuable insights for the genetic improvement and conservation of Hippophae species.